Hair cell ribbon synapses - Moser, Tobias; Brandt, Andreas; Lysakowski, Anna (Cell and tissue research, 2006)
Hearing and balance rely on the faithful synaptic coding of mechanical input by the auditory and vestibular hair cells of the inner ear. Mechanical deflection of their stereocilia causes the opening of mechanosensitive channels, resulting in hair cell depolarization, which controls the release of glutamate at ribbon-type synapses. Hair cells have a compact shape with strong polarity. Mechanoelectrical transduction and active membrane turnover associated with stereociliar renewal dominate the apical compartment. Transmitter release occurs at several active zones along the basolateral membrane. The astonishing capability of the hair cell ribbon synapse for temporally precise and reliable sensory coding has been the subject of intense investigation over the past few years. This research has been facilitated by the excellent experimental accessibility of the hair cell. For the same reason, the hair cell serves as an important model for studying presynaptic Ca²⁺ signaling and stimulus-secretion coupling. In addition to common principles, hair cell synapses differ in their anatomical and functional properties among species, among the auditory and vestibular organs, and among hair cell positions within the organ. Here, we briefly review synaptic morphology and connectivity and then focus on stimulus-secretion coupling at hair cell synapses.